2017
DOI: 10.1115/1.4037938
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Roles of Muscles, Passive Prostheses, and Powered Prostheses During Sloped Walking in People With a Transtibial Amputation

Abstract: Sloped walking is challenging for individuals with transtibial amputation (TTA) due to the functional loss of the ankle plantarflexors. Prostheses that actively generate ankle power may help to restore this lost function. The purpose of this study was to use musculoskeletal modeling and simulation to quantify the mechanical power delivered to body segments by passive and powered prostheses and the remaining muscles in the amputated and intact legs during sloped walking. We generated walking simulations from ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Therefore, it is possible that a powered ankle-foot prosthesis that can only replace the function of the uni-articular soleus is incapable of fully replicating biological ankle function during walking. Furthermore, musculoskeletal modeling studies have found that the use of powered or passive-elastic prostheses increases whole-body sagittal plane angular momentum compared to non-amputees and that neither device is capable of providing power to the trunk similar to the biological gastrocnemius (Pickle et al, 2016(Pickle et al, , 2017. Future studies should investigate the mechanical energy loss and transfer from the prosthetic ankle to the residual limb, and investigate the role of the socket-limb interface in this energy transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is possible that a powered ankle-foot prosthesis that can only replace the function of the uni-articular soleus is incapable of fully replicating biological ankle function during walking. Furthermore, musculoskeletal modeling studies have found that the use of powered or passive-elastic prostheses increases whole-body sagittal plane angular momentum compared to non-amputees and that neither device is capable of providing power to the trunk similar to the biological gastrocnemius (Pickle et al, 2016(Pickle et al, , 2017. Future studies should investigate the mechanical energy loss and transfer from the prosthetic ankle to the residual limb, and investigate the role of the socket-limb interface in this energy transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Use of the powered prosthesis normalized metabolic cost while walking on level ground and normalized trailing leg step-to-step transition work on both level ground and a 5° uphill ramp (Russell Esposito et al, 2016). Use of the powered compared to passive-elastic prosthesis reduced hamstring muscle activation on uphill slopes of +3°, +6°, and +9° (Pickle et al, 2017) and reduced the range of sagittal plane whole-body angular momentum on slopes of −10°, −5°, 0°, and +5° (Pickle et al, 2016). It remains unclear how use of a powered ankle-foot prosthesis affects leg joint work contributions during uphill and downhill walking over a range of slopes compared to use of a passive-elastic prosthesis.…”
mentioning
confidence: 99%
“…Yet despite these biomechanical limitations of active prostheses, the issue is further complicated by studies finding that users prefer an active prosthesis over a passive one 3 . The discrepancy between quantitative biomechanical measures and qualitative user feedback suggests that it is important to consider not only local joint mechanics (e.g., prosthetic ankle power generation) or lumped whole-body measures (e.g., net metabolic energy expenditure, step-to-step transition work 5 , range of H ) but also the effects of the device on segmental coordination during gait 1517 . Here, we define “coordination” as the contributions of individual segments to whole-body movement at specific times during a movement.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ]. Several previous studies have used optimal control methods [ 8 , 9 , 15 18 ] and other related methods [ 19 ] to simulate limb loss gait, but have not modeled changes in muscle strength with limb loss, and it is unknown how various levels of bilateral or unilateral (residual limb) muscle strength loss affect the metabolic cost of walking post-limb loss.…”
Section: Introductionmentioning
confidence: 99%